Insect Management for Legumes (Beans, Peas) - Susan E. Webb (EDIS)
Many different insects attack leguminous vegetables. Aphids damage terminals, whiteflies feed on sap and transmit bean golden mosaic virus, and caterpillars like bean leafroller and beetles feed on leaves. Flower thrips feed in blossoms and stink bugs, corn earworm, and leaffooted bugs damage seeds and pods. This document is ENY-465 (IG151), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2002. Revised: August 2005.